Battlefield acupuncture for chronic musculoskeletal pain in cancer survivors: a novel care delivery model for oncology acupuncture - Zhang, Yi Lily; Mao, Jun J.; Li, Q. Susan; Weitzman, Matthew; Liou, Kevin T. (Frontiers in Pain Research, 2023)
Introduction Battlefield Acupuncture (BFA), a standardized auricular acupuncture protocol, is widely used for pain in the military but is not well-studied in oncology. This study examined cancer survivors who received BFA for pain. Methods This is a secondary analysis of a randomized trial that compared the effectiveness of BFA and electroacupuncture vs. usual care for chronic musculoskeletal pain in cancer survivors. This study focused on participants randomized to BFA. Participants received 10 weekly treatments. Needles were placed until one of these stop conditions were satisfied: ten needles were administered; pain severity decreased to ≤1 out of 10; patient declined further needling, or vasovagal reaction was observed. Pain severity was assessed using Brief Pain Inventory. Responders were those with ≥30% pain severity reduction. We examined pain location, BFA stop reason, and pain reduction of participants during the first session. We also examined which factors predicted responder status after the first session (week 1) or the full treatment (week 12). Results Among 143 randomized to BFA, most common pain locations were lower back (30.8%) and knee/leg (18.2%). Of 138 who initiated treatment, 41 (30.0%) received ten needles; 81 (59.1%) achieved pain ≤1; 14 (10.2%) declined further needling; and 1 (0.7%) had vasovagal reaction. BFA reduced pain severity by 2.9 points (95% CI 2.6 to 3.2) after the first session (P < 0.001). After adjusting for baseline pain severity, responders at week 1 were 2.5 times more likely to be responders at week 12, compared to those who were non-responders at week 1 (AOR 2.5, 95% CI 1.02 to 6.11, P = 0.04). Among those who achieved pain ≤1, 74% were responders at week 12, a higher proportion compared to the proportion of responders among those who received ten needles (39.5%), those who declined further needling (50%), and those with vasovagal reaction (0.0%) (P = 0.001). Those with pain in proximal joints had a higher proportion of responders at week 12, compared to those with pain in distal joints (64.2% vs. 20%, P = 0.008). Conclusion Specific factors may predict the likelihood of achieving meaningful pain reduction from BFA. Understanding these predictors could inform precision pain management and acupuncture delivery models.